Strategic Public Relations Leadership. - Gregory, Anne (Taylor and Francis, 2013)
Public relations is operating in an increasingly challenging and complex environment. Pressures from outside the organisation include new accountabilities, empowered stakeholders, increased public cynicism and a new communication landscape. Internally, there are increasing demands to demonstrate a return on investment, alongside a requirement to coach and counsel senior managers exposed to these environmental pressures. This context requires public relations professionals to be able to clearly articulate and demonstrate their own contribution to organisational effectiveness. T.